Las multinacionales están arrasando con la biodiversidad de América Latina y de Ecuador en particular, las madereras, estractoras de palmas de aceite, hidroelectricas, petroleras y mineras en general, por lo que es necesario que las leyes ambientales protejan en forma efectiva estos recursos - Jumbo Pineda, Edgar Geovanny (2012)
Legal research is part of academic issues within the environmental law, and particularly of the Environment Law, Forest Law, Water Law, Law of Hydrocarbons, etc. , So academically justified because it meets the requirements established by the Academic Board Regulations National University of Loja, which regulates relevance of the study, research legal issues inherent to matters of positive law, to qualify for the degree Attorney. On the other hand, aims to demonstrate the need for effective protection of the state in safeguarding the fundamental legal security of citizens through this specific case to prevent the destruction of the environment by transnational logging companies, oil, hydro, construction. It follows therefore that the issue is important and social and legal significance to be investigated in an attempt to solve the problem posed to the State and the environment. With the application of methods: Scientist, inductive, deductive, analytical, statistical, using techniques and procedures as the signing bibliographic survey, interview, case analysis is feasible socio‐legal research of the problem proposal, while there are sources of bibliographic, documentary and field that will provide analysis and discussion, then, has the necessary logistical support and methodological guidance necessary for causal explanatory and critical study of the problem.